Analysis of Organic Fertilizer Marketing Strategy at the Indmira Company to Meet the Needs of Palm Oil Farmers in Kuantan Singingi Regency Using the SWOT Method - Wibawadi, Yanuar; Muslichah, Istyakara (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to analyze the marketing of organic liquid fertilizer at the Indmira Company in meeting the needs of Kuantan Singingi oil palm farmers using the SWOT method. The type of research used in this research is qualitative research. The research was carried out at PT. Indmira selected 32 respondents and resource persons from Kuantan Singingi Regency. The data collection techniques used were interview techniques and questionnaires. The results of the research show that using SWOT analysis, Indmira's organic liquid fertilizer product has the opportunity to increase sales of liquid organic fertilizer through outreach and introduction, as well as building cooperation and using information technology regarding the product in the people of Kuantan Singingi Regency. The results of respondents' answers showed a good perception of organic liquid fertilizer. There are several factors that make this organic fertilizer have a good perception, one of which is that organic fertilizer has a long-term effect on the health of palm trees and the price is still affordable. Some farmers believe that organic liquid fertilizer is an environmentally friendly product. The results of the questionnaire explained that respondents were interested in using organic liquid fertilizer as an alternative or as a distraction from chemical fertilizers. This is because organic liquid fertilizer is a green product or environmentally friendly fertilizer. Organic fertilizer has a long-term effect on the health of palm trees, reduces environmental pollution and is more affordable.